A personagem em José Saramago: dialética e humanismo - Garlet, Deivis Jhones; Umbach, Rosani Ketzer (Navegações, 2018)
Ao reconhecer a dialética e o humanismo como princípios de construção estética em José Saramago, propomos um estudo da categoria narrativa da personagem na obra do autor, com o objetivo de explicitar seu funcionamento e seu acabamento axiológico. Partiremos do paradigma de que a explicação do literário – aqui em relação à personagem – necessita partir do interior do universo ficcional, isto é, a função que exerce na estrutura da obra. Com esse paradigma de investigação, advogaremos em defesa do funcionamento dialético da personagem; da sua constituição dialógica, intimamente relacionada a sua dialeticidade; e da articulação da vida da personagem quanto ao eixo semântico humanista-democrático, todos esses três elementos inter-relacionados de modo a construir uma certa cosmovisão de vida, de Homem. Para tornar o argumento mais sólido, recorreremos a alguns pressupostos de análise da personagem já tradicionais, como as propostas de Hamon, de Forster e de Bakhtin. *** The character in José Saramago: dialectic and humanism *** In recognizing the dialectic and humanism as principles of aesthetic construction of José Saramago, we propose a study of the narrative category of the character in the author’s work, with the purpose of explaining its functioning and its axiological finishing. We will start from the paradigm that the explanation of the literary – here in relation to the character – needs to start from the interior of the fictional universe, that is, the function that it exerts in the structure of the work. With this paradigm of investigation, we will advocate in defense of the dialectical functioning of the character; of its dialogical constitution, closely related to its dialectic; And of the articulation of the life of the person in relation to the humanist-democratic semantic axis, all three interrelated elements in order to construct a certain worldview of life, of Man. To make the argument more solid, we will resort to some of the traditional assumptions of character analysis, such as the proposals of Hamon, Forster and Bakhtin. Keywords: Character; Dialectic; Humanism.